2012
DOI: 10.1017/s1368980012004326
|View full text |Cite
|
Sign up to set email alerts
|

At the crossroads: new paradigms of food security, public health nutrition and school food

Abstract: Public health nutrition sits at the nexus of a global crisis in food, environmental and health systems that has generated -along with numerous other problemsan urgent and changing problem of food insecurity. The 'new' food insecurity, however, is different from the old: it is bimodal, encompassing issues of both under-and over-consumption, hunger and obesity, quantity and quality; it has assumed a decidedly urban dimension; and it implicates rich and poor countries alike. The complexity of the expressions of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 41 publications
1
39
0
2
Order By: Relevance
“…‘quantity’); it also encompasses problems of over‐ and mal‐consumption – or, as Lang (, 95) states, ‘all diet‐related ill health, not just hunger’. In short, food insecurity is fundamentally a bimodal problem of malnutrition (Ashe and Sonnino ) that affects over one‐quarter of the world's population in both the global North and the developing South. This juxtaposition of hunger and obesity is complicating efforts to design an effective food security agenda.…”
Section: Reclaiming the Local In Food Security Debates: The Contextmentioning
confidence: 99%
“…‘quantity’); it also encompasses problems of over‐ and mal‐consumption – or, as Lang (, 95) states, ‘all diet‐related ill health, not just hunger’. In short, food insecurity is fundamentally a bimodal problem of malnutrition (Ashe and Sonnino ) that affects over one‐quarter of the world's population in both the global North and the developing South. This juxtaposition of hunger and obesity is complicating efforts to design an effective food security agenda.…”
Section: Reclaiming the Local In Food Security Debates: The Contextmentioning
confidence: 99%
“…A number of studies have suggested that policy makers may need to counter some of the nancial constraints faced by individuals, schools, and communities in order to lift compliance with school food policies (15,68,69), for instance by reducing reliance on canteen revenue for school maintenance, or offering grants or reward programs (74). There is also scope to facilitate programs to empower and create economic opportunities for local communities by incentivising schools to source foods from local producers (10). As suggested by participants themselves, schools need political support to prevent food vendors from operating around the perimeter and to restrict the movement of children during school hours.…”
Section: Addressing Policy Barriers For Actors Responsible For Implemmentioning
confidence: 99%
“…The concept of a nutrition-promoting school is holistic, in that a supportive setting might in uence the ethos of the whole school community (9). Schools that promote the consumption of healthy FNAB can contribute to food security, stimulating local food production and the local economy (10), and the public procurement of food is increasingly viewed as an opportunity to promote policy coherence (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…; Sonnino ). As part of a ‘systems’ approach to food security, mediated markets involving targeted food procurement and distribution aim to address the structural determinants of food security through a reduction in food price volatility (a challenge for both urban consumers and rural producers) and the maintenance of vibrant domestic food supply chains (Ashe and Sonnino ).…”
Section: Introductionmentioning
confidence: 99%
“…1 More broadly, Home-Grown School Feeding programmes (HGSF) have emerged as an opportunity to support rural sustainable development and meet food security and educational challenges by facilitating social and economic relations between targeted populations of producers and consumers (Bagdonis et al 2008;Rocha 2009;Otsuki 2011;Sumberg and Sabates-Wheeler 2011;Buckley et al 2013;Quaye et al 2013;Sonnino 2013). As part of a 'systems' approach to food security, mediated markets involving targeted food procurement and distribution aim to address the structural determinants of food security through a reduction in food price volatility (a challenge for both urban consumers and rural producers) and the maintenance of vibrant domestic food supply chains (Ashe and Sonnino 2013).…”
Section: Introductionmentioning
confidence: 99%